Application of active anti-floating in underground structure based on automatic drainage system. Issue 1 (January 2021) - Li, Junxin; Zhu, Guoliang; Wang, Jinbing; Zeng, Ping
Abstract: With the continuous rapid development of China's economy and the rapid progress of urbanization, the development and utilization of urban underground space continues to develop downward, and the problem of anti-floating of underground structures is increasingly prominent. Passive anti-floating methods will continue to increase engineering costs while increasing structural resistance. The anti-float method reduces the base buoyancy while reducing the project cost accordingly. Through "plus" and "minus" comparative study, the advantages of the active anti-floating method for underground structures based on automatic drainage systems are highlighted, combined with specific engineering practices and application effects. To further confirm the advantages of the active anti-floating method for underground structures based on automatic drainage systems.